OH-Initiated Photooxidations of 1-Pentene and 2-Methyl-2-propen-1-ol: Mechanism and Yields of the PrimaryCarbonyl Products - Peirone, Silvina Anahí (2014)
The products of the gas-phase reactions of OH radicals with 1-pentene and 2-methyl-2-propen-1-ol (221MPO) at T=298±2 K and atmospheric pressure were investigated by using a 4500 L atmospheric simulation chamber that was built especially for this work. The molar yield of butyraldehyde was 0.74±0.12 mol for the reaction of 1-pentene. This work provides the first product molar yield determination of formaldehyde (0.82±0.12 mol), 1-hydroxypropan-2-one (0.84±0.13 mol), and methacrolein (0.078±0.012 mol) from the reaction of 221MPO with OH radicals. The mechanism of this reaction is discussed in relation to the experimental results. Additionally, taking into consideration the complex mechanism, the rate coefficients of the reactions of OH with formaldehyde, 1-hydroxypropan-2-one, and methacrolein were derived at atmospheric pressure and T=298±2 K.; the obtained values were (8.9±1.6)×10−12, (2.4±1.4)×10−12, and (22.9±2.3)×10−12 cm3 molecule−1 s−1, respectively.